The Effects of Personal Values on Online Buying Intention - Ang, Yvonne S. M. (Advances in Social Sciences Research Journal, 2023)
E-commerce has emerged to be pervasive channel as consumers continue to adopt the use of digitally enabled technologies to make online purchases. In developing nations, digital commerce continues to gain prominence. This study examines the influence of personal values on online consumer purchase. Using the Theory of Human Values and the Unified Theory of Acceptance and Use of Technology 2 (UTAUT2), the effects of personal values Self-Direction, Hedonism, Achievement and Security on the constructs in technology adoption (UTAUT2) model were investigated. Data for this study was collected from 424 respondents and analysed using structural equation modeling. The results show that Self-Direction, Security, Achievement and Hedonism influence various constructs in the UTAUT2 model. Notably, Self-Direction, Security and Hedonism influenced Effort Expectancy and Facilitating Conditions. While Achievement and Hedonism influenced Habit. This elucidates the influence of multiple personal values on the consumer’s motivation towards the performance of online shopping, specifically, to master skills needed (Effort Expectancy), obtain support (Facilitating Conditions) and repeat online buying behaviour (Habit). The findings hope to shed insight on the influence of personal values on the consumers’ motivation to use online purchasing; allowing e-commerce managers to improve consumer communication and digital strategies.